Aeronautical Meteorology Glossary: a discussion on term definition in the ANACpedia termbase - Peixoto, Rafaela Araújo Jordão Rigaud (The ESPecialist, 2020)
In this paper, the study of terminological definitions in specialized fields, particularly the aviation field, is proposed. During the development of a glossary for the Aeronautical Meteorology subfield, in English and in Portuguese, for the ANACpedia database, there was a need to delineate specificities with the purpose to meet the expectations of a varied audience. Based on Finatto (2001) regarding types of definition and standardization guidelines prescribed by ISO 704/1987, this paper (1) analyzes procedures for the extraction of definitions and the organization of ANACpedia structural classes, and (2) discusses the termbase macro-organization and definitional categories used. In this way, nuances of terminological definition choices for the Aeronautical Meteorology subfield were discussed, with the purpose of contributing to improve the elaboration of entries for specialized glossaries.